2019
DOI: 10.1080/0144929x.2019.1680732
|View full text |Cite
|
Sign up to set email alerts
|

‘Age Matters’: A panel study investigating the influence of communicative and passive smartphone use on well-being

Abstract: Communicative and passive online use have been shown to affect individuals' well-being in opposite ways. While communicative use is often associated with beneficial outcomes, passive use may even harm individuals' well-being. However, existing studies have paid insufficient attention to the influence of age on these associations. Additionally, little evidence is available regarding the impact of communicative and passive smartphone use on individuals' well-being across the lifespan. Drawing upon the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 86 publications
4
31
0
Order By: Relevance
“…The HPC is one of the first structures to show atrophic changes with age [16]. In addition, a decline in sensory abilities is common in aging; thus, place learning may be impaired when there are HPC and sensory changes due to aging effects [2,17]. These results are consistent with previous studies that addressed statements of individual difference [18][19][20] and task-type effects [11].…”
Section: Age and Task-type Differencesupporting
confidence: 89%
See 2 more Smart Citations
“…The HPC is one of the first structures to show atrophic changes with age [16]. In addition, a decline in sensory abilities is common in aging; thus, place learning may be impaired when there are HPC and sensory changes due to aging effects [2,17]. These results are consistent with previous studies that addressed statements of individual difference [18][19][20] and task-type effects [11].…”
Section: Age and Task-type Differencesupporting
confidence: 89%
“…The young group scored higher than the senior group did. Thus, there was a significant effect of gender on navigational performance in the young group, but not in the senior group [2]. This result partially aligns with previous claims that males may perform better than females in VR wayfinding tasks [5,13], but that this difference may disappear due to other interactive effects.…”
Section: Age and Gender Differencessupporting
confidence: 87%
See 1 more Smart Citation
“…For the older age group (55+ years), positive affect was additionally shown to be a relevant mediator (see Chan, 2018 ). In another recent study, Stevic et al (2019) found that passive smartphone use negatively predicted life satisfaction four months later for participants regardless of age, while communicative smartphone use was positively related with life satisfaction four months later only for participants older than 63. This implies that different age groups seem to rely on their smartphones for different reasons, an observation which might also transfer to the context of coping.…”
Section: Introductionmentioning
confidence: 90%
“…Social media usage patterns as well as smartphone use are still very different between age groups with younger participants being usually more active and using more features ( Fortunati & Taipale, 2014 ; Smith & Anderson, 2018 ). Additionally, it has been shown that the use of communication applications was associated with well-being differently and through different pathways for different age groups ( Chan, 2018 ; Stevic, Schmuck, Matthes, & Karsay, 2019 ). While for the younger age group (18–34 years), civic engagement mediated the effect between multimodal connectedness and well-being, this relationship was mediated by individual social capital for the middle age group (35–54 years).…”
Section: Introductionmentioning
confidence: 99%